Deconstruction of the Legend “Putri Tujuh”: Reproduction of the Meaning of Marriage Hierarchy in Contemporary Malay Society - Elmustian; Ika Apriyanti (International Journal of Technology and Education Research, 2026)
Folktales are often viewed as static entities that serve only as conservative didactic media. This study aims to deconstruct the legend of "Putri Tujuh" from Dumai to uncover the shifting sociocultural paradigm related to Malay marriage traditions. Using descriptive qualitative methods and Jacques Derrida's deconstructive analysis, this study dismantles the binary opposition between customary obedience (hereditary hierarchy) and the reality of life (theological inclusivity). The results show an aporia in the text that has marginalized the role of individual will in favor of structure. The new meaning discovered is the transformation of the "langkah bendul" phenomenon from a sociological disgrace into a form of "sovereignty of destiny" (theological). This finding reconstructs the identity of modern Malay society that is more adaptive, empathetic, and inclusive without abandoning its religious essence.